An Investigation of the Quality of Online Science Education at the Tertiary Level from the Perspectives of Students, Instructors and University Administrators - Colby, Stephanie Mae-Fawcett (Curtin University, 2021)
This qualitative interview study investigated perceptions of quality held by university administrators, instructors and students of online science courses. The stakeholder groups had differing priorities when evaluating quality; their perceptions were highly dependent on context including the specific science discipline, whether the course was designed for science majors or non-majors, and laboratory goals. This study suggests all stakeholders’ perspectives and educational contexts be considered for constructive discussion of quality in online science courses.